Association of Socioeconomic Factors and Sedentary Lifestyle in Belgrade's Suburb, Working Class Community - Slavica KONEVIC; Jelena MARTINOVIC; Nela DJONOVIC (Tehran University of Medical Sciences, 2015)
Background: Sedentary lifestyle represents a growing health problem and considering that there is already a range of unhealthy habits that are marked as health risk factors and the increasing prevalence of sedentary lifestyle worldwide, we aimed to investigate association of sedentary way of living in suburb, working class local community with socioec-onomic determinants such as educational level, occupation and income status. Methods: In this community-based cross-sectional study, 1126 independently functioning adults were enrolled into the study. The study protocol included a complete clinical and biochemical investigation revealing age, gender, lipid status, height, weight and blood pressure. Trained interviewers (nurses) collected information from patients about cur-rent state of chronic diseases (diabetes mellitus, arterial hypertension) smoking, medication and other socioeconomic data. Descriptive analysis, Chi-square and logistic regression were performed as statistical calculations. Results: Patients with elementary school were seven times more likely to be classified in category with sedentary life-style compared to patients with college or faculty degree. Being retired and reporting low income were significantly associated with higher odds of sedentary behavior when compared with students and patients with high-income status, respectively. Conclusions: The significance of this study lies in the fact that our results may help to easier identification of patients who may have a tendency towards a sedentary lifestyle.